A macro-element approach to analyse bridge abutments accounting for the dynamic behaviour of the superstructure. Issue 8 (16th August 2020) - Gorini, Davide Noè; Callisto, Luigi
Abstract : This paper describes an original approach to the study of the seismic behaviour of bridge abutments. The proposed method incorporates a simplified description of the dynamic response of the bridge structure into a finite-element model of the soil–abutment system. Specifically, the dynamic behaviour of the bridge structure is described by a macro-element that simulates the loads transferred to the abutment during the seismic event. The macro-element is identified using a structural model of the bridge as a reference. This approach improves the current analysis methods based on sub-structuring, limiting at the same time the computational demand needed for a complete study of the soil–structure interaction. In the paper, the validity of the procedure is demonstrated comparing the results of the simplified approach with the results obtained from full three-dimensional dynamic analyses of idealised soil–bridge systems, using non-linear advanced constitutive models to describe the soil behaviour. Based on these results, a strategy is devised for the calibration of the bridge macro-element, making use of a limited number of input parameters.